Modelling the Dissociation Dynamics and Threshold Photoelectron Spectra of Small Halogenated Molecules - Harvey, Jonelle; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Jonelle Harvey$1 (Bs thesis outlines two related experimental techniques which are utilised to investigate small halogenated molecules: threshold photoelectron spectroscopy and threshold photoelectron photoion coincidence techniques. All the experiments were conducted at the vacuum ultraviolet beamline of the Swiss Light Source, which is a synchrotron photon source offering easy tunability. In this thesis, three studies are presented which combine experimental and computational ab initio approaches. The first study involves the fast dissociation of halogenated methanes in order to construct a self-consistent thermochemical network. The second study investigates the fragmentations of fluoroethenes from timebombs, which break apart very slowly but explosively, to fast dissociators. The third study uncovers how vital conical interactions underpin both the results of photoelectron spectra and dissociation patterns.The details included in this work are useful for researchers in the same field as well as those readers wishing to obtain a solid introduction into the types of systems encountered in threshold photoelectron photoion coincidence spectroscopy.s
From the Contents: Introduction -- Measuring the photoelectron signal -- The study of ionic dissociations -- Thermochemistry -- Experimental -- The synchrotron radiation source -- The endstation -- Capturing the electron signal -- The experimental results -- Theory -- Computational methods -- Modelling.
Keywords: Chemistry; Chemistry, Physical organic; Chemistry; Physical Chemistry; Atomic/Molecular Structure and Spectra; Theoretical and Computational Chemistry